2019
DOI: 10.1021/acschemneuro.8b00680
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of mTOR Activation-Mediated Upregulation of Synapsin II and Neurite Outgrowth to Hyperalgesia in STZ-Induced Diabetic Rats

Abstract: Painful diabetic neuropathy (PDN) is among the common complications in diabetes mellitus (DM), with its underlying mechanisms largely unknown. Synapsin II is primarily expressed in the spinal dorsal horn, and its upregulation mediates a superfluous release of glutamate and a deficiency of GABAergic interneuron synaptic transmission, which is directly implicated in the facilitation of pain signals in the hyperalgesic nociceptive response. Recently, synapsin II has been revealed to be associated with the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…31 Similarly, our recent finding demonstrated that mTOR signaling is essential for the development of painful diabetic neuropathy. 16 Here, we also observed the activation of mTOR signaling in the spinal cord, as indicated by the elevation in the p-mTOR and p-S6K (a downstream effector of mTOR). However, these alterations could be reversed by i.t.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…31 Similarly, our recent finding demonstrated that mTOR signaling is essential for the development of painful diabetic neuropathy. 16 Here, we also observed the activation of mTOR signaling in the spinal cord, as indicated by the elevation in the p-mTOR and p-S6K (a downstream effector of mTOR). However, these alterations could be reversed by i.t.…”
Section: Resultssupporting
confidence: 60%
“…18,19 Our recent study has found that mTOR plays a vital role in diabetes-related neuropathic pain. 16 Thus, we detected the phosphorylation level of p-mTOR at ser2448 and its downstream S6K. 20 Furthermore, we found that the protein levels of p-mTOR and p-S6K were We also analyzed the production of pro-inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The phosphorylation of mTOR and p70S6K in the spinal dorsal horn is increased in neuropathic pain models and administration of the mTOR inhibitor rapamycin effectively mitigates hyperalgesia in these models, in that context, QUER could alleviate neuropathic pain by inhibiting mTOR/p70S6K pathway‐mediated changes in synaptic morphology and synaptic function, as demonstrated in an experimental model of diabetic neuropathy (Wang et al, 2020). Another mechanism by which QUER generates a decrease in sensitivity in this work could be explained by its effect on the regulation of the P2X4 receptor (Yang et al, 2019), since the P2X4 receptor contributes to inflammatory pain and neuropathic pain (Cho et al, 2018; He et al, 2019; Wang et al, 2020) and studies have shown that peripheral nerve injury can increase the expression and activation of P2X4 in the DRG as a key factor in the initiation and sustained development of neuropathic pain (Yang et al, 2019; Ying et al, 2017). In summary, these mechanisms favor the decrease in hypersensitivity shown in CCI rats when QUER is administered.…”
Section: Discussionmentioning
confidence: 86%